Perceptual Accent Rating and Attribution in Psychogenic FAS: Some Further Evidence Challenging Whitaker’s Operational Definition - Keulen, Stefanie; Verhoeven, Jo; Bastiaanse, Roelien; Mariën, Peter; Jonkers, Roel; Mavroudakis, Nicolas; Paquier, Philippe (Frontiers in Human Neuroscience, 2016)
A 40-year-old, non-aphasic, right-handed, and polyglot (L1: French, L2: Dutch, L3: English) woman with a 12 year history of addiction to opiates and psychoactive substances, and clear psychiatric problems, presented with a foreign accent of sudden onset in L1. Speech evolved towards a mostly fluent output, despite a stutter-like behavior and a marked grammatical output disorder. The psychogenic etiology of the accent foreignness was construed based upon the patient’s complex medical history, and psychodiagnostic, neuropsychological, and neurolinguistic assessments. The presence of a foreign accent was affirmed by a perceptual accent rating and attribution experiment. It is argued that this patient provides additional evidence demonstrating the outdatedness of Whitaker’s (1982) definition of Foreign Accent Syndrome, as only one of the four operational criteria was unequivocally applicable to our patient: her accent foreignness was not only recognized by her relatives and the medical staff, but also by a group of native French-speaking laymen. However, our patient defied the three remaining criteria, as central nervous system damage could not conclusively be demonstrated, psychodiagnostic assessment raised the hypothesis of a conversion disorder, and the patient was a polyglot whose newly gained accent was associated with a range of foreign languages, which exceeded the ones she spoke.